Gold(I)-catalyzed synthesis of β-Kdo glycosides using Kdo ortho-hexynylbenzoate as donor. (7th August 2017) - Mi, Xuemeng; Lou, Qixin; Fan, Wenjing; Zhuang, Liqin; Yang, You
Abstract: A gold(I)-catalyzed glycosylation of Kdo with glycosyl ortho -hexynylbenzoate as donor is reported. The couplings of Kdo ortho -hexynylbenzoate with a set of alcohols promoted by PPh3 AuOTf afford Kdo glycosides with good β-selectivities. This glycosylation method allows for the synthesis of β-Kdo monosaccharide with a C5 linker at the reducing end for subsequent conjugation to carrier proteins and arrays. Graphical abstract: Highlights: A gold(I)-catalyzed glycosylation with Kdo ortho -hexynylbenzoate as donor is described. The Kdo glycosides were obtained with excellent β-selectivities. Synthesis of β-Kdo monosaccharide with a C5 linker at the reducing end is achieved.